Analisis Pengaruh Penerapan Sistem Informasi Rujukan Terintegrasi (Sisrute) Terhadap Kinerja Karyawan Rsud Meuraxa Kota Banda Aceh - Imilda; Andalia, Tjut Ira Rizki; Ahmad, Adi (Jurnal Sistem Komputer (SISKOM), 2024)
This research aims to analyze the effect of implementing the Integrated Referral Information System (SISRUTE) on employee performance at Meuraxa Regional Hospital, Banda Aceh City. In the context of developments in information technology, SISRUTE has become an important innovation in the health referral system. However, there are still challenges in implementing it in hospitals. This research uses a descriptive analysis method by collecting data through surveys and statistical analysis. The research results show that even though SISRUTE has been implemented, its effect on employee performance is not yet significant. This shows the need for further efforts to increase the effectiveness of SISRUTE implementation at Meuraxa District Hospital.